2.3k views
1 vote
Which of the following is equivalent to (2x + 3)(2x + 3)?

Which of the following is equivalent to (2x + 3)(2x + 3)?-example-1
User A Poor
by
5.1k points

2 Answers

4 votes

Answer:


(2x+3)(2x+3)=4x^2+12x+9

Explanation:

we are given


(2x+3)(2x+3)

Firstly, we will distribute it


=2x* 2x+2x* 3+3* 2x+3* 3

now, we can simplify it


=2* 2* x* x+2* 3x+3* 2x+9


=4x^2+6x+6x+9


=4x^2+12x+9

so, we get simplified term as


(2x+3)(2x+3)=4x^2+12x+9

User Carlos Pisarello
by
4.6k points
2 votes

Answer:


Explanation:

Identity : (a + b)² = a² + 2ab + b²

It is given that,

(2x + 3 )(2x + 3)

we can write (2x + 3 )(2x + 3) = (2x + 3)²

It is similar to the identity.

Here a = 2x and b = 3

Therefore,

(2x + 3)² = (2x)² + 2 *2x*3 + 3²

= 4x² + 12x +9

Therefore the correct answer is option A. 4x² + 12x +9

User Zen
by
5.4k points